2022
DOI: 10.3390/cells11142171
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cells from Patients with Rheumatoid Arthritis Are Characterized by Reduced Expression of Ikaros Zinc Finger Transcription Factors

Abstract: Regulatory T (Treg) cells play an important role in immune tolerance and contribute to the prevention of autoimmune diseases, including rheumatoid arthritis (RA). The differentiation, function and stability of Treg cells is controlled by members of the Ikaros zinc finger transcription factor family. In this study, we aimed to reveal how the expression of Ikaros transcription factors is affected by disease activity in RA. Therefore, we analyzed the ex vivo expression of Ikaros, Helios, Aiolos and Eos in Treg ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…IKZF3 (Aiolos) and IKZF2 (Helios), and BACH2 have been implicated in other autoimmune disease such as systemic lupus erythematosus (SLE) and Rheumatoid Arthritis (RA) [25,[31][32][33][34][35][36]. In this study, the expression of these genes was increased in severe cases of CFS and greater upregulation was observed in those who suffer from comorbid autoimmune diseases, suggesting that CFS is, in part, an autoimmune disease.…”
Section: Cfs and T Cell And B Cell Functionsmentioning
confidence: 85%
“…IKZF3 (Aiolos) and IKZF2 (Helios), and BACH2 have been implicated in other autoimmune disease such as systemic lupus erythematosus (SLE) and Rheumatoid Arthritis (RA) [25,[31][32][33][34][35][36]. In this study, the expression of these genes was increased in severe cases of CFS and greater upregulation was observed in those who suffer from comorbid autoimmune diseases, suggesting that CFS is, in part, an autoimmune disease.…”
Section: Cfs and T Cell And B Cell Functionsmentioning
confidence: 85%
“…IKZF3 is a member of the IKAROS family and plays an important role in the maturation of B and T cells, [9,10] it has been reported in hematopoietic malignancies, immunological diseases, and solid tumors. [11][12][13][14] However, the association of IKZF3 expression with HNSCC has not been reported. This is the first study to explore the prognostic value of IKZF3 expression in HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Aiolos is a zinc finger transcription factor (TF), encoded by IKZF3, that has a broad impact on gene expression patterns by activating chromatin modifiers like nucleosome remodeling and deacetylase complexes. [9,10] In more recent years, the crucial value of IKAROS family zinc finger members (IKZF) has been increasingly recognized in immune diseases and solid tumors, [11,12] and research in hematopoietic malignancies has been initially identified as evidence for the participation of the IKAROS family in carcinoma progression. [13,14] Mounting evidence suggests that the immune system plays a crucial role in tumorigenesis, growth, and metastasis, and immune-related genes are believed to be associated with tumor prognosis.…”
Section: The Study Was Funded By Basic Public Welfare Project Of Ning...mentioning
confidence: 99%
“…IKZF3 (Aiolos) and IKZF2 (Helios), and BACH2 have been implicated in other autoimmune disease such as systemic lupus erythematosus (SLE) and Rheumatoid Arthritis (RA) [22,[28][29][30][31][32][33].…”
Section: Cfs and T Cell And B Cell Functionsmentioning
confidence: 99%